Decoding the role of gut microbiota in Alzheimer’s pathogenesis and envisioning future therapeutic avenues - Liang, Junyi; Liu, Bin; Dong, Xiaohong; Wang, Yueyang; Cai, Wenhui; Zhang, Ning; Zhang, Hong (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) emerges as a perturbing neurodegenerative malady, with a profound comprehension of its underlying pathogenic mechanisms continuing to evade our intellectual grasp. Within the intricate tapestry of human health and affliction, the enteric microbial consortium, ensconced within the milieu of the human gastrointestinal tract, assumes a role of cardinal significance. Recent epochs have borne witness to investigations that posit marked divergences in the composition of the gut microbiota between individuals grappling with AD and those favored by robust health. The composite vicissitudes in the configuration of the enteric microbial assembly are posited to choreograph a participatory role in the inception and progression of AD, facilitated by the intricate conduit acknowledged as the gut-brain axis. Notwithstanding, the precise nature of this interlaced relationship remains enshrouded within the recesses of obscurity, poised for an exhaustive revelation. This review embarks upon the endeavor to focalize meticulously upon the mechanistic sway exerted by the enteric microbiota upon AD, plunging profoundly into the execution of interventions that govern the milieu of enteric microorganisms. In doing so, it bestows relevance upon the therapeutic stratagems that form the bedrock of AD’s management, all whilst casting a prospective gaze into the horizon of medical advancements.